Method for packaging perovskite quantum dots by photon sintering
By combining mesoporous silica nanoparticles with photonic sintering technology, uniform dispersion and encapsulation of quantum dots at the submicron scale were achieved, solving the problems of uneven encapsulation and agglomeration in existing technologies, improving optical performance and stability, simplifying the process, and reducing costs.
Patent Information
- Application Number
- CN202510700696.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-28
- Publication Date
- 2025-10-31
AI Technical Summary
Existing quantum dot encapsulation technologies struggle to achieve uniform dispersion at the micron and submicron scales, leading to agglomeration, reduced optical performance, and complex processes that increase commercialization costs, thus limiting the application of quantum dot materials in high-performance display and lighting devices.
Mesoporous silica nanoparticles are used as encapsulation materials. Quantum dots are uniformly dispersed and encapsulated at the submicron scale through photonic sintering. The porous structure is used for confined growth to avoid agglomeration, and photonic sintering is used for rapid encapsulation.
This technology enables high-quality encapsulation of quantum dots at the submicron scale, avoiding aggregation, improving optical performance and stability, simplifying processes, and reducing commercialization costs.
Smart Images

Figure CN120865884A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of quantum dot optical film technology, and in particular to a method for encapsulating perovskite quantum dots using photonic sintering. Background Technology
[0002] Lead-cetium halide perovskite quantum dots (CsPbX3 PQDs, X = Cl, Br, I, and mixtures thereof) possess excellent optical properties, including tunable size and bandgap, strong light absorption coefficient, high quantum yield, and narrow full width at half maximum (FWHM), making them a hot research topic in the field of optoelectronics. The chemical stability and physical integrity of the quantum dot surface determine its optical properties. However, their applications have always been limited due to their sensitivity to moisture and oxygen and their tendency to quench. Therefore, improving the stability of all-inorganic halide perovskite quantum dots is urgently needed.
[0003] Researchers typically encapsulate all-inorganic halide perovskite quantum dots to ensure their stability in applications. Encapsulation technology introduces a protective layer on or around the quantum dot to isolate it from external environmental interference, thereby improving its stability, luminous efficiency, and lifespan. Furthermore, encapsulation technology can improve the integration and patterning capabilities of quantum dots in devices, which is particularly important for high-resolution, full-color displays.
[0004] Professor Zhong Haizheng's team at Beijing Institute of Technology prepared perovskite quantum dots embedded in polymer microspheres using a spray-drying method, leveraging the flexibility of polymers. This not only improved the dispersibility of the quantum dots but also enhanced their stability in complex environments. Metal-organic frameworks (MOFs), with their structural diversity, tunable channels, and customizable functionalization, have become ideal host materials for encapsulating perovskites. Encapsulation prevents perovskite aggregation and mitigates external environmental stimuli, thereby increasing its stability.
[0005] Inorganic materials (such as silicon dioxide and metal oxides) are widely used in quantum dot encapsulation due to their high chemical stability and good optical transparency. A research team at Nanjing University of Science and Technology has developed a superhydrophobic perovskite quantum dot luminescent pixel array. By coating the surface of quantum dots with fluorinated silicon dioxide particles, they have achieved excellent self-cleaning ability and photoluminescence performance (Ziyi Chen, et al., Nano Lett., 2025, 25, 2568.).
[0006] Existing quantum dot encapsulation technologies have significantly improved the stability of quantum dots. However, current encapsulation techniques struggle to achieve micron and submicron scale encapsulation, limiting the uniform dispersion and resolution of quantum dot materials. Furthermore, agglomeration is unavoidable during encapsulation, leading to reduced optical performance. Additionally, the complex processes involved in current quantum dot encapsulation technologies cannot be completed quickly. This not only restricts the application of quantum dot materials in high-performance display and lighting devices but also increases their commercialization costs. Therefore, achieving high-quality quantum dot encapsulation at the submicron scale and avoiding the optical performance degradation caused by agglomeration is crucial. Summary of the Invention
[0007] To address the aforementioned technical problems, this invention provides a method for encapsulating perovskite quantum dots using photonic sintering. This invention employs mesoporous silica nanoparticles as the encapsulation material, utilizing a porous structure for confined growth to uniformly disperse the quantum dots within a sub-micron scale, achieving precise size control and preventing quantum dot aggregation. The photonic sintering process achieves quantum dot encapsulation through rapid energy transfer. This process can complete sintering in milliseconds, reducing surface traps and oxidation reactions that may be introduced during traditional thermal annealing, further improving the optical performance and stability of the quantum dots.
[0008] This invention is achieved through the following technical solution:
[0009] The purpose of this invention is to provide a method for encapsulating perovskite quantum dots using photonic sintering, comprising the following steps:
[0010] (1) Preparation of a suspension of mesoporous silica nanoparticles;
[0011] (2) The suspension obtained in step (1) is coated onto the substrate surface and dried to form a uniform array of mesoporous silica nanoparticles on the substrate surface.
[0012] (3) Immerse the substrate obtained in step (2) in a perovskite precursor solution, sonicate and crystallize to obtain a quantum dot crystal substrate;
[0013] (4) The substrate obtained in step (3) is photonic sintering encapsulated.
[0014] In one embodiment of the present invention, in step (1), the particle size of the mesoporous silica nanoparticles in the suspension of the mesoporous silica nanoparticles is 50-80 nm; the pore size of the mesopores is 3-5 nm.
[0015] In one embodiment of the present invention, in step (1), the concentration of the mesoporous silica nanoparticles in the suspension is 5-10 mg / mL; the solvent is 10 vol% acetone: 90 vol% ethanol.
[0016] In one embodiment of the present invention, in step (2), the substrate is selected from one or more of quartz wafers, silicon wafers and solar cells.
[0017] In one embodiment of the present invention, in step (2), the coating is performed by dip-coating method; the dip time is 8 to 10 minutes and the coating rate is 500 μm / s.
[0018] In one embodiment of the present invention, in step (2), the drying conditions are: drying at room temperature for 3 to 5 minutes.
[0019] In one embodiment of the present invention, in step (3), the perovskite precursor solution is an organic solution containing CsBr and PbBr2 at a concentration of 50 mM.
[0020] In one embodiment of the present invention, in step (3), the conditions for crystallization are: vacuum degree ≤ 200 Pa, crystallization temperature 60℃~160℃.
[0021] In one embodiment of the present invention, in step (4), the light source for photonic sintering is selected from a xenon lamp with a voltage of 1000-1100V.
[0022] In one embodiment of the present invention, in step (4), the flash energy density of the sintered material is 17.25–17.75 J / cm². 2 .
[0023] In one embodiment of the present invention, in step (4), the number of photon sintering operations is 25.
[0024] The technical solution of the present invention has the following advantages compared with the prior art:
[0025] This invention provides a method for encapsulating perovskite quantum dots using photonic sintering. The porous structure of silica mesoporous nanoparticles provides a confined space for the quantum dots, enabling them to be uniformly dispersed within a 50 nm scale. This avoids size inconsistencies and agglomeration of the quantum dots, ensuring a narrow emission peak.
[0026] Photonic sintering is a short-time, high-energy sintering technology that can achieve encapsulation within 5 minutes, ensuring the dispersion of silica nanoparticles while simultaneously achieving encapsulation. This is beneficial for the subsequent application of quantum dots in high-performance optoelectronic devices and imaging fields. Attached Figure Description
[0027] To make the content of this invention easier to understand, the invention will be further described in detail below with reference to specific embodiments and accompanying drawings, wherein:
[0028] Figure 1This is a schematic diagram of the photonic sintering and encapsulation process for perovskite quantum dots in this invention;
[0029] Figure 2 These are scanning electron microscope (SEM) images of perovskite quantum dots encapsulated in the mesopores of silica particles on a quartz substrate using photonic sintering, according to the present invention; wherein, A is a transmission electron microscope (TEM) image; and B is a scanning electron microscope (SEM) image.
[0030] Figure 3 These are photoluminescence images of perovskite quantum dots obtained from different sintering times during the performance testing of this invention;
[0031] Figure 4 These are photoluminescence images of perovskite quantum dots obtained at different crystallization temperatures during the performance testing of this invention;
[0032] Figure 5 This is an electron microscope image of silica particles under traditional high-temperature sintering and encapsulation technology in the performance testing of this invention. Detailed Implementation
[0033] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, so that those skilled in the art can better understand and implement the present invention. However, the embodiments described are not intended to limit the present invention.
[0034] This invention prepares perovskite@CsPbBr3 quantum dots based on template-free mesoporous silica nanoparticles:
[0035] First, template-free mesoporous silica nanoparticles are uniformly dispersed on the substrate surface. To ensure uniform particle distribution, a suspension of nanoparticles is coated onto the substrate surface using an dip-coating method, and after drying, a uniform array of mesoporous silica nanoparticles is formed. Figure 1 The flowchart is shown.
[0036] The present invention describes the confined growth of quantum dots within the mesopores of silica nanoparticles:
[0037] A substrate coated with mesoporous silica nanoparticles was immersed in a perovskite precursor solution. The substrate was sonicated for 1 minute to allow the precursor solution to fully penetrate the mesoporous structure of the silica particles. The impregnated substrate was then placed in a vacuum drying oven, with the vacuum level controlled below 200 Pa. The crystallization temperature was 100–160 °C to achieve uniform crystallization of the perovskite precursor within the silica mesopores.
[0038] This invention involves photonic sintering and encapsulating quantum dots:
[0039] After the quantum dots crystallize, the substrate is placed in a photonic sintering chamber, and the photonic sintering parameters are adjusted to high voltage and repeated multiple times. During the sintering process, due to the high energy density of the flash, the temperature of the silica nanoparticles can reach their melting point (approximately 1000–1200°C) in a short time, causing the mesopores of the silica nanoparticles to collapse, achieving the encapsulation effect.
[0040] Unless otherwise specified, the experimental methods used in the following examples are conventional methods, and the materials and reagents used are commercially available.
[0041] Example 1
[0042] This embodiment provides a method for encapsulating perovskite quantum dots using photonic sintering. The flowchart of this method is shown below. Figure 1 As shown, the specific steps are as follows:
[0043] (1) Preparation of perovskite@CsPbBr3 quantum dots based on template-free mesoporous silica nanoparticles
[0044] First, template-free mesoporous silica nanoparticles were uniformly dispersed on the substrate surface: To ensure uniform particle distribution, a suspension of mesoporous silica nanoparticles (particle size 50 nm; pore size 5 nm) (10 mg / mL, solvent 10 vol% acetone: 90 vol% ethanol) was coated onto the substrate quartz sheet surface by dip-coating method. The dip-coating time was 600 s, the coating rate was 500 μm / s, and after drying at room temperature for 4 min, a uniform array of mesoporous silica nanoparticles was formed.
[0045] (2) Confined growth of quantum dots in the mesopores of silica nanoparticles
[0046] CsBr and PbBr2 were dissolved in DMSO to obtain a 50 mM perovskite precursor solution. A substrate coated with mesoporous silica nanoparticles was immersed in the perovskite precursor solution and sonicated for 1 min to allow the precursor solution to fully penetrate the mesoporous structure of the silica particles. The impregnated substrate was then placed in a vacuum drying oven with the vacuum level controlled below 200 Pa, the crystallization temperature at 120 °C, and the time at 12 h to achieve uniform crystallization of the perovskite precursor within the silica mesopores and to evaporate the organic solvent.
[0047] (3) Photonic sintering encapsulation of quantum dots
[0048] After the quantum dots crystallized, the substrate was placed in a photonic sintering cavity, and the photonic sintering parameters were adjusted to a high voltage (1100V) and repeated 25 times. During the sintering process, due to the high energy density of the flash (17.5±0.25J / cm²), 2The temperature of silica nanoparticles can reach their melting point (approximately 1000–1200°C) within a short time (<5 min), causing the mesopores of the silica nanoparticles to collapse and achieving an encapsulation effect.
[0049] Example 2
[0050] This embodiment provides a method for encapsulating perovskite quantum dots using photonic sintering, similar to Embodiment 1, except that the crystallization temperature in step (2) is 60°C, and the rest of the operation is the same.
[0051] Example 3
[0052] This embodiment provides a method for encapsulating perovskite quantum dots using photonic sintering, similar to Embodiment 1, except that the crystallization temperature in step (2) is 160°C, and the rest of the operation is the same.
[0053] Example 4
[0054] This embodiment provides a method for encapsulating perovskite quantum dots using photonic sintering, similar to Embodiment 1, except that the substrate is replaced with a silicon wafer, while the rest of the operation is the same.
[0055] Comparative Example 1
[0056] This comparative example provides a method for encapsulating perovskite quantum dots using photonic sintering, similar to Example 1, except that the number of photonic sintering operations in step (3) is 0.
[0057] Comparative Example 2
[0058] This comparative example provides a method for encapsulating perovskite quantum dots using photonic sintering, similar to Example 1, except that the number of photonic sintering operations in step (3) is 30.
[0059] Comparative Example 3
[0060] This comparative example provides a method for encapsulating perovskite quantum dots using photonic sintering, similar to Example 1, except that the number of photonic sintering operations in step (3) is 35.
[0061] Performance Test 1
[0062] The scanning electron microscope image of the photonic sintered encapsulated perovskite quantum dots prepared in Example 1 is shown below. Figure 2 As shown, by Figure 2 It can be seen that the porous structure of silica mesoporous nanoparticles provides a confined space for quantum dots, enabling them to be uniformly dispersed within a 50nm scale, avoiding size inconsistencies and agglomeration of quantum dots, thus ensuring the narrow emission peak of quantum dots.
[0063] Performance Test 2
[0064] The photonic sintered encapsulated perovskite quantum dots obtained in Examples 1, 1, 2, and 3 were washed with water, and then photoluminescence was measured using a near-infrared / visible fluorescence spectrometer. The results are as follows: Figure 3 As shown. (Through) Figure 3 It can be seen that the QDs in the samples that have not undergone photonic sintering are immediately quenched upon contact with water, while the samples that have undergone 25 and 30 photonic sintering cycles have their QDs encapsulated due to the collapse of the mesopores, thus still exhibiting photoluminescence after water washing. This indicates that the perovskite quantum dots still exhibit fluorescence after water washing, and the silica coating effectively isolates the quantum dots from water, thus providing an encapsulation effect. However, excessive sintering cycles (such as 35 cycles) will cause the samples to absorb too much energy, and the excessively high sintering temperature will lead to the high-temperature quenching of the QDs.
[0065] Performance Test 3
[0066] The photonic sintered encapsulated perovskite quantum dots obtained in Examples 1-3 were washed with water and then subjected to photoluminescence testing. The results are as follows: Figure 4 As shown, it can be seen that crystallization of CsPbBr3 is feasible within this temperature range.
[0067] In traditional high-temperature sintering encapsulation technology, the agglomeration of silica particles is inevitable.
[0068] (like Figure 5 As shown in the diagram, this increases particle scattering and reduces resolution in further applications. However, in the method of this invention, nanoparticle structures can be fabricated on the substrate first and then encapsulated by photonic sintering, avoiding agglomeration. Furthermore, photonic sintering, due to its weak penetrating power, has minimal impact on the substrate, thus preventing substrate failure.
[0069] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.
Claims
1. A method for encapsulating perovskite quantum dots using photonic sintering, characterized in that, Includes the following steps: (1) Preparation of a suspension of mesoporous silica nanoparticles; (2) The suspension obtained in step (1) is coated onto the substrate surface and dried to form a uniform array of mesoporous silica nanoparticles on the substrate surface. (3) Immerse the substrate obtained in step (2) in a perovskite precursor solution, sonicate and crystallize to obtain a quantum dot crystal substrate; (4) The substrate obtained in step (3) is photonic sintering encapsulated.
2. The method according to claim 1, characterized in that, In step (1), the mesoporous silica nanoparticles in the suspension have a particle size of 50-80 nm and a pore size of 3-5 nm.
3. The method according to claim 1, characterized in that, In step (1), the concentration of the mesoporous silica nanoparticles in the suspension is 5-10 mg / mL.
4. The method according to claim 1, characterized in that, In step (2), the substrate is selected from one or more of quartz wafers, silicon wafers and solar cells.
5. The method according to claim 1, characterized in that, In step (2), the coating is performed using the dip-coating method; the dip time is 8 to 10 minutes.
6. The method according to claim 1, characterized in that, In step (2), the drying conditions are: drying at room temperature for 3 to 5 minutes.
7. The method according to claim 1, characterized in that, In step (3), the conditions for crystallization are: vacuum degree ≤ 200 Pa, crystallization temperature 60℃~160℃.
8. The method according to claim 1, characterized in that, In step (4), the light source for photonic sintering is selected from a xenon lamp with a voltage of 1000-1100V.
9. The method according to claim 1, characterized in that, In step (4), the flash energy density of the sintered material is 17.25–17.75 J / cm². 2 .
10. The method according to claim 1, characterized in that, In step (4), the photon sintering is performed 25 times.
Citation Information
Cited By
Perovskite aerogel yarn and preparation method and application thereof
CN121931649A
Perovskite aerogel yarn and preparation method and application thereof
CN121931649B